Application of technical analysis indicators on a market data - Tabiš, Peter; Trešl, Jiří, 1947-2011; Bašta, Milan; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2011)
The purpose of the thesis is test of current technical analysis indicators with the support of basic statistical software (Excel and PASW STATISTICS). During the test we will apply the correlation process in order to find two less similar markets. Subsequently, we will use these markets for testing the individual indicators of the analysis. The chosen indicators are those of the highest popularity as far as the profit/loss analysis is considered.
Vedoucí práce: Jiří Trešl
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2011
Rok obhajoby 2011
Keywords: statistické metody v ekonomii [obor bakal. práce]; bakalářské práce; bachelor's theses